2016
DOI: 10.1007/s11011-016-9891-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of resveratrol and environmental enrichment on biomarkers of oxidative stress in young healthy mice

Abstract: Resveratrol (RESV) and Environmental Enrichment (EE) have been separately reported to protect organisms against various diseases. This study investigated the potential benefit of the combination of RESV and EE on biomarkers of oxidative stress in young healthy mice. Fifty mice of both sexes were randomly divided into five groups of 10 animals each: group I served as control, group II were maintained on alternate day feeding, group III received RESV 50 mg/kg, suspended in caboxymethylcellulose orally per kg/day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 55 publications
0
12
0
Order By: Relevance
“…Previously, some studies had already reported the protective potential of EE on maintenance of redox homeostasis. EE showed to prevent DNA oxidation ( Kang et al, 2016 ; Sun et al, 2016 ), the increase of carbonyl protein ( Herring et al, 2008 ), the increase of total free radicals content ( Cechetti et al, 2012 ) and the increase of lipid peroxidation ( Muhammad et al, 2017 ) in rodents.…”
Section: Resultsmentioning
confidence: 99%
“…Previously, some studies had already reported the protective potential of EE on maintenance of redox homeostasis. EE showed to prevent DNA oxidation ( Kang et al, 2016 ; Sun et al, 2016 ), the increase of carbonyl protein ( Herring et al, 2008 ), the increase of total free radicals content ( Cechetti et al, 2012 ) and the increase of lipid peroxidation ( Muhammad et al, 2017 ) in rodents.…”
Section: Resultsmentioning
confidence: 99%
“…Only its interaction with other risk factors, such as environmental stress or NMDAR-hypofunction on other neurons in the circuit leads to schizophrenia-related deficits. One mechanism as to how environmental stress may interact with the risk factor of NMDAR-hypofunction in interneurons could involve metabolic stress: it has been well documented that reduced environmental enrichment increases oxidative stress levels in rodents (Cechetti et al, 2012; Muhammad et al, 2017) and that NMDAR-hypofunction in PV-interneurons in the mouse line we used in this study renders those interneurons more vulnerable to oxidative stress (Jiang et al, 2013a,b). Finally, for the clinical realm, our data encourages the establishment of a stimulating and stress-free environment to improve symptoms in schizophrenia (Rogers et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, when submitted to EE, the pilocarpine group did not differ from the saline group. This once again indicates that environmental enrichment had a neuroprotective effect, attenuating the damage caused by oxidative stress 20 , which is normally induced by pilocarpine 17 . These results reinforce the hypothesis that EE improves the metabolic response of the cerebral cortex during CSD.…”
Section: Glutamatementioning
confidence: 70%
“…In relation to oxidative processes, it is described that EE is able to attenuate oxidative stress and strengthen antioxidant protection mechanisms 19,20 . Another mechanism reported in the literature suggests that EE stimulates the serotonergic system and an increase in brain serotonin levels is related to a reduction in the speed of the spread of CSD 21 .…”
Section: Glutamatementioning
confidence: 99%